METODE QIYAS SEBAGAI LANDASAN EPISTEMOLOGI NAHWU - Nana Jumhana (Al Qalam, 2014)
Qiyas (analogy) is one of several methods which had been used by Arabic linguist since the first generation until those who lived in the second century of Hijriyah in formulating Arabic grammars next to Sama' (orally transmitted material). The formulation of the grammars was aimed at conservating Arabic from any kinds of inference, considering that it was not only a mere treasure of the Arab, but also language of Islam after the revelation of Alqur'an. As an ephistemological basis of Arabic synthax, Qiyas serves as an analogy to some eloquent saying of the ancient Arabs. In so doing, Qiyas consists of four components: 1) maqis 'alaih (the source to which one thing is comparred), 2) maqis (the respected object to be comparred), 3) 'illah (the similar aspectls the both share), and 4) hukm (the verdict in search). In terms of it's kind, linguists devide it into three kinds: 1) qiyas al' illah, 2) qiyas at-tard, and qiyas as-syibhi. Even though some linguists argue against the using of Qiyas in formulating grammars, particularly for it is not in line with sima', also for it is considered to be built on subjective rationalisation, Qiyas is of great significance in language theorizing. The significance of Qiyas is not limited to the products demonstrated by traditional linguists. It also applies to our time too, particularly in developing Arabic language in all of it's aspects. Keyword: Qiyas, Method, Taq id al-Nahwi, Mazhab Basrah, Mazhab Kufah